Integrating Islamic Character Education Through The Bina Pribadi Islami Program: An Evidence-Based Model For Bullying Prevention In Indonesian Secondary Schools - Ilham Akhyar Musthofa; Istanto (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
Bullying in schools is a serious problem that negatively impacts the psychological, social, and academic development of students. This study aims to analyze the effectiveness of the Islamic Personal Development Program (BPI) at SMPIT Al Huda Wonogiri as a preventive strategy in addressing bullying through a character development approach based on Islamic values. Using a qualitative research method with a case study design, data were collected through interviews, observations, and documentation, then analyzed thematically. The results of the study indicate that BPI, implemented systematically through coaching students, teachers, and parents, is able to reduce the frequency and intensity of bullying, and create a safe, empathetic, and religious school climate. The approach of spiritual education, habituation of worship, role models, and active student participation has proven effective in internalizing the values of monotheism, good morals, empathy, and responsibility. This study provides a theoretical contribution by strengthening the moral concepts of Al-Ghazali, Ibn Miskawaih, and Lickona's character education theory. The conclusion of the study confirms that spirituality-based character education has great potential as a bullying prevention model that can be replicated in various schools. It is recommended that further research explore the application of this model in different social and cultural contexts and measure its long-term impact.